The effectiveness of the popular scientific book Dayak Ngaju ethnopharmacology in Pendahara Village to train students' critical thinking abilities - Rio Rajamia Harlinson; Danang Biyatmoko; Aminuddin Prahatama Putra (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
One effort that can be made to build students' critical thinking skills is to develop popular scientific books (PSB) that are systematic and easy for students to understand. This research aims to describe the effectiveness of the PSB Ethnopharmacology in Pendahara Village, Ngaju Dayak Community Area, for Training Students' Critical Thinking Skills. The development stage includes self-evaluation, expert testing, individual testing, small group testing, and field testing. The research subjects were five students for the small group test and 20 for the field test. The effectiveness of PSB is analyzed descriptively. The research results show that the developed PSB was declared effective. Based on this data, the average N-Gain value is 0.5, resulting in a medium N-Gain category. Base on this research results, it can be concluded that the PSB on ethnopharmacology in Pendahara Village, Ngaju Dayak Community Area, is effectively used in training students' critical thinking skills.Abstrak Salah satu usaha yang dapat dilakukan dalam membangun keterampilan berpikir kritis mahasiswa adalah mengembangkan buku ilmiah popular (BIP) yang sistematis dan mudah dipahami mahasiswa. Penelitian ini bertujuan mendeskripsikan keefektifan BIP Etnofarmakologi Desa Pendahara Kawasan Masyarakat Dayak Ngaju untuk Melatihkan Keterampilan Berpikir Kritis Mahasiswa. Tahap pengembangan meliputi evaluasi diri, uji pakar, uji perorangan, uji kelompok kecil, uji lapangan. Subjek penelitian adalah 5 mahasiswan untuk uji kelompok kecil dan 20 mahasiswa untuk uji lapangan. Keefektifan BIP dianalisis secara deskriptif. Hasil penelitian menunjukan BIP yang dikembangkan dinyatakan efektif. Berdasarkan data tersebut maka nilai rerata N-Gain 0,5 sehingga diperoleh kategori N-Gain sedang. Berdasarkan hasil penelitian ini dapat disimpulkan bahwa BIP etnofarmakologi Desa Pendahara Kawasan Masyarakat Dayak Ngaju efektif digunakan dalam melatih keterampilan berpikir kritis mahasiswa.